Study of the Effects of Urban Morphology on Physical Activity - Braçe, Olta (Revista de Estudios Andaluces, 2016)
A large number of studies, mainly conducted in Anglo-Saxon and northern European countries, have found correlations between urban morphology and transport-related physical activity (walking and cycling). From these studies it appears as urban areas of high density, with mixed-uses, lack of services, different transit options and high-quality public spaces reduce automobile dependence and increase the opportunities for transport-related physical activity. This article explore the association between urban design variables and physical activity, showing as the results obtained in a European Mediterranean area (municipality of Mairena del Aljarafe) are consistent with the scientific literature. This makes it possible to affirm that in our environment there is also relationship between urban sprawl, physical activity and use of transport-related physical activity (walking and cycling). These results should serve for urban and territorial planners and managers take measures aimed at preventing the progressive increase sprawl areas and promoting central areas. These measures will help reduce car dependence, increasing transport-related physical activity, and maintaining the three pillars of sustainable development (economic, social and environmental).